Sustainable management of marine resources through customary practices: The implementation of sasi on sea cucumbers in Werka Village, Maluku Province - Hajar Suryawati Siti; Pramoda Radityo; Miftakhul Huda Hakim; Sri Nastiti Adriani; Pujiyani Astuti Lismining; Steward Samusamu Andrias; Rahman Arip; Rahmanov Zedta Raymon; Puspasari Reny; Rahmia Anwar Putri Masayu (BIO Web of Conferences)
Natural resource management based on local wisdom is a key approach to effective and sustainable biodiversity conservation outside protected areas. One example is the sasi practice for sea cucumbers in Werka Village, Southeast Maluku Regency, Maluku Province. This study examines the application of Traditional Ecological Knowledge (TEK) in sasi practices to sustain sea cucumber populations. The research aims to analyze the implementation of sasi in Werka Village, the role of indigenous peoples, and the challenges they face in resource conservation. Data were collected through interviews and analyzed using qualitative scoring and a descriptive case study approach. The findings indicate that the success of sasi in Werka Village is driven by the integration of economic, social, and institutional factors, with strong support from indigenous communities and local authorities.